LEARNING INNOVATION IN THE 21ST CENTURY AND ITS IMPLEMENTATION IN IMPROVING STUDENTS' KNOWLEDGE - Saimima, M Sahrawi; Adu, La (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2024)
Abstrack: Education in the 21st century has experienced a very significant development in terms of learning. The purpose of this writing is to express what innovation activities have been carried out by educators in increasing student knowledge through analysis conducted by the author on various article sources that discuss similar topics. The research method used in writing is a descriptive research method fengan type of literature. This method is used to collect and analyze learning resources through articles on various journal houses. The results of this study show that learning innovation is carried out with a number of methods used such as flipped learning, blanded learning, e learning, project based learning, online method, offline method, home visit and so on. In addition, educators also use a number of applications as media in the learning process such as watshaap, gogle classroom, zoom and gogle meet. As for these processes, it can increase students' knowledge to, 1) conduct learning independently with their friends, 2) have knowledge in operating technology, 3) Follow learning anywhere, 4) Students easily access learning resources.